Climate change and class conflict in the Anthropocene: sink or swim together?. Issue 1 (2nd January 2023) - Arsel, Murat
ABSTRACT: Class is key to understanding the genesis and impacts of climate change. Nevertheless, it is commonly argued that 'we are all in the same ship', suggesting that emerging climate politics will not be conflictual along class lines. This paper demonstrates that (agrarian) political economy and political ecology scholars have not adequately scrutinized the relevance of class to contemporary environmental politics to counteract such claims. It also briefly considers two questions – can there be progress without conflict? and can there be conflict without an enemy? – before calling for the development of a Marxist theory of environmental conflicts in the Anthropocene.